Development and Validation of a Questionnaire on Knowledge and Attitude Toward Far-Infrared-Emitting Garments, Their Medical Applications and Health Benefits - Md Azahri, Nor Saadah; Taib, Ibrahim Adham; Nor Azmi, Haizatul Umiyah (International Journal of Allied Health Sciences, 2025)
Introduction: Infrared radiation is a form of energy within the electromagnetic spectrum, categorized by its frequency and wavelength. Far-infrared (FIR)-emitting garments such as blankets, belts, clothing, and socks infused with bio-ceramic powder are commercially available and have been associated with various health benefits in scientific literature. However, no studies have yet explored the public’s knowledge, attitude, and practice (KAP) regarding the use of FIR-emitting garments. This highlights the need for a valid and reliable instrument to assess these components. Objective: The primary objective of this study was to develop and validate a questionnaire to assess knowledge and attitudes toward FIR-emitting garments, including their medical applications and health benefits. Methodology: The development process included both validity and reliability assessments. Five experts conducted face and content validity evaluations based on item relevance, clarity, simplicity, and ambiguity. The Content Validity Index (CVI) was calculated using both the Item-level (I-CVI) and Scale-level (S-CVI) indices. A pilot test involving 51 respondents was carried out to determine internal consistency using Cronbach’s Alpha. Results: The CVI scores for knowledge items averaged 0.88, with with I-CVI and S-CVI values averaging 0.88 across all evaluated criteria. For attitude items, the I-CVI and S-CVI values averaged 0.84 for relevance and 0.87 for clarity, simplicity, and ambiguity. The reliability analysis yielded Cronbach’s Alpha values of 0.807 for knowledge items and 0.745 for attitude items. Conclusion: The developed questionnaire demonstrated strong content validity (CVI > 0.83) and acceptable internal consistency (Cronbach’s Alpha > 0.73). Therefore, the instrument is considered valid and reliable for assessing knowledge and attitudes related to FIR-emitting garments and their potential health benefits. It is recommended for use in future population-based studies.